ANALISIS UU NO.1 TAHUN 1974 TENTANG PERKAWINAN DAN UU NO. 23 TAHUN 2002 TETANG PERLINDUNGAN ANAK TERKAIT PERKAWINAN DIBAWAH UMUR (STUDI PADA MASYARAKAT BATU LAYAR PROVINSI GORONTALO) - Bakung, Dolot Alhasni (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2014)
Negative effects of the implementation of the marriage to minors who are often carried out by a number of public as well as to the other party is very large, especially in the child's psychological, so the need for treatment for the prevention of execution serisu underage marriage either caused by the environment until a match to date this is often done by a number of people residing in remote areas. With the Law No. 23 of 2002 on Protection of Children and the Law No. 1 of 1974 About Marriage, the need for restrictions on underage marriage.